Infarcts in the posterior circulation territory in migraine. The population-based MRI CAMERA study - Kruit, Mark C.; Launer, Lenore J.; Ferrari, Michel D.; van Buchem, Mark A. (Brain (London, England : 1878), 2005)
In a previous study, migraine cases from the general population were found to be at significantly increased risk of silent infarct-like lesions in the posterior circulation (PC) territory of the brain, notably in the cerebellum. In this study we describe the clinical and neuroimaging characteristics of migraine cases with and without aura and controls with PC lesions. In total, 39 PC infarct-like lesions represented the majority (65%) of all 60 identified brain infarct-like lesions in the study sample (n = 435 subjects with and without migraine). Most lesions (n = 33) were located in the cerebellum, often multiple, and were round or oval-shaped, with a mean size of 7 mm. The majority (88%) of infratentorial infarct-like lesions had a vascular border zone location in the cerebellum. Prevalence of these border zone lesions differed between controls (0.7%), cases with migraine without aura (2.2%) and cases with migraine with aura (7.5%). Besides higher age, cardiovascular risk factors were not more prevalent in cases with migraine with PC lesions. Presence of these lesions was not associated with supratentorial brain changes, such as white matter lesions. The combination of vascular distribution, deep border zone location, shape, size and imaging characteristics on MRI makes it likely that the lesions have an infarct origin. Previous investigators attributed cases of similar ‘very small’ cerebellar infarcts in non-migraine patients to a number of different infarct mechanisms. The relevance and likelihood of the aetiological options are placed in the context of known migraine pathophysiology. In addition, the specific involvement of the cerebellum in migraine is discussed. The results suggest that a combination of (possibly migraine attack-related) hypoperfusion and embolism is the likeliest mechanism for PC infarction in migraine, and not atherosclerosis or small-vessel disease.